2016
DOI: 10.1590/1516-4446-2015-1874
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of fine motor dexterity in mild cognitive impairment and Alzheimer’s disease dementia: association with activities of daily living

Abstract: Objective: Cognitive impairment is a hallmark of mild cognitive impairment (MCI) and Alzheimer's disease dementia (AD). Although the cognitive profile of these patients and its association with activities of daily living (ADLs) is well documented, few studies have assessed deficits in fine motor dexterity and their association with ADL performance. The objective of this research paper is to evaluate fine motor dexterity performance among MCI and AD patients and to investigate its association with different asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 24 publications
7
62
0
2
Order By: Relevance
“…We found that reduced dexterity as well as poor cognitive function were significantly associated with patient age, which is confirmed by the existing literature on the topic [14,23,24]. As expected and mirrored by the existing literature, dexterity and cognitive function were also inversely correlated [23,24].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that reduced dexterity as well as poor cognitive function were significantly associated with patient age, which is confirmed by the existing literature on the topic [14,23,24]. As expected and mirrored by the existing literature, dexterity and cognitive function were also inversely correlated [23,24].…”
Section: Discussionsupporting
confidence: 89%
“…As expected and mirrored by the existing literature, dexterity and cognitive function were also inversely correlated [23,24]. Interestingly, neither dexterity nor cognitive function seem to affect overall HRQoL in UD patients.…”
Section: Discussionsupporting
confidence: 85%
“…The results herein strengthen the need to take careful considerations in defining the requirements of a task into the assessment of motor control of depressed individuals as there are indirect evidences that frontal lobe dysfunctions present a considerable association with the interaction between aging*depression intensity as well with depression intensity itself. Furthermore, ours findings may have clinical implications since the determination of mechanisms that leads to disability in aging are extremely important for the elaboration of preventive measures to help maintain their functional capability 52,53 . It adds evidence to support the claim that the progression of depressive symptoms deserves a closer look when the disorder is established.…”
Section: Discussionmentioning
confidence: 91%
“…In this respect, further reliability study including raters of similar proficiency in MFT may be warranted. Lastly, although fine motor skill is mostly affected by age in non-demented elders (Hoogendam et al 2014), cognitive deficit may influence dexterity (de Paula et al 2016). Since we did not evaluate cognitive function in our healthy participants, any influence by cognitive deficits may not be excluded especially in our older participants.…”
Section: Study Limitationsmentioning
confidence: 99%